Clinical Indications Of Vasakarishta An Experiential And Scientific View - Shripathi, Acharya G; Acharya, Miss Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2021)
Asavarishta preparations are commonly used in the clinical practice by Ayurveda physicians in India and Indian subcontinent. Among these, Pippalyasava, Pushkaramoolasava, Dashamoolarishta, Kanakasava, Kutajarishta, Kumari Asava, Mustakarishta, Draksharishta, Usheerasava, Abhayarishta are few formulations which are commonly used by physicians in the management of various non communicable diseases . Vasakarishta is one such preparation which is used in the management of chronic respiratory disorders. It is usually used in Acute bronchitis, chronic bronchitis, bronchial asthma, URTI, LRTI, Pratishyaya , Peenasa, deviated nasal septum , chronic repeated sneezing , (Kshavathu), Kasa, Shwasa, Raktapitta, Rajayakshma, bronchiectasis , emphysema and cor pulmonale , . It is having the actions like dipana (appetizer), pachana (digestive), bronchodilator, expectorant, Kasaghna, Shwasahara, antibacterial , bactericidal , anti-infective , immunomodulator , immunity booster, antistress , adaptogenic and mucolytic in action . The present paper highlights about the therapeutic indications of Vasakarishta in experiential and scientific view.